2016
DOI: 10.3389/fmicb.2016.01243
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Polymorphisms within NFκB-Related Genes and the Risk of Developing Invasive Aspergillosis

Abstract: Invasive Aspergillosis (IA) is an opportunistic infection caused by Aspergillus, a ubiquitously present airborne pathogenic mold. A growing number of studies suggest a major host genetic component in disease susceptibility. Here, we evaluated whether 14 single-nucleotide polymorphisms within NFκB1, NFκB2, RelA, RelB, Rel, and IRF4 genes influence the risk of IA in a population of 834 high-risk patients (157 IA and 677 non-IA) recruited through a collaborative effort involving the aspBIOmics consortium and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…The five remaining genes included in our research (CCL2, CCR2, CD209, CLEC6A, CLEC6A) were previously subjected to case-control studies concerning aspergillosis. However, even the most comprehensive of those studies included only a limited number of the known SNPs [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The five remaining genes included in our research (CCL2, CCR2, CD209, CLEC6A, CLEC6A) were previously subjected to case-control studies concerning aspergillosis. However, even the most comprehensive of those studies included only a limited number of the known SNPs [7].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of those studies, a limited number of genetic polymorphisms were reported whose associations with aspergillosis were replicated and/or proved to have biological significance [reviewed in 6]. However, the majority of the studies concerning candidate genes concentrated on a limited number of single nucleotide polymorphisms (SNPs), employing low-or medium-throughput genotyping strategies [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In another study that focused specifically on recipients of solid-organ transplants, genome-wide association study analysis led to the identification of IL-1β and β-defensin 1 as essential for limiting fungal colonization and/or infection [69] . Finally, a recent study examining genes in the NF-κB family found that, despite identifying an SNP in IRF4 that was associated with a 6-fold increased risk of developing IA, this did not reach statistical significance [70] . Table 1 summarizes new findings in the area of innate host defense mechanisms during IA in the last 3-5 years.…”
Section: Genome-wide Association Studiesmentioning
confidence: 93%
“…However, it should be indicated that it is not a trivial question to find out a concentration that inhibits NFkB activation and pro-inflammatory cytokine production in macrophages, independently of GT-mediated killing, at least in mouse macrophages (Unpublished data), which might affect the proper interpretation of these findings. However, the relevance of these findings in humans is not clear, since a recent study has shown that SNP in different molecules of NFkB pathway do not increase the risk of IA in SCT patients ( 91 ). Thus, in order to clarify the role of GT-mediated NFkB inhibition during IA, studies comparing NFkB activity during infection with GT producing and non-producing A. fumigatus strains should be carried out.…”
Section: Immunosuppressive Activity Of Gliotoxinmentioning
confidence: 99%